Traffic-related impacts on air quality around student housing in Malang, Indonesia - Muhammad Evan Wahyudi Putra; Ridwan Muhamad Rifai; Mohammad Palwa Priya Rajendra (Center for Science and Technology, Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Urban air pollution from traffic emissions poses a significant risk to students residing in student communal housing (SCH) near major roadways. This study investigates the impact of peak hour traffic on ambient air quality around SCH in Malang City, focusing on carbon dioxide (CO₂), total volatile organic compounds (TVOC), and fine particulate matter (PM2.5). Measurements were taken at 40 SCH locations during both daytime and nighttime peak hours. The study employed Geographic Information Systems (GIS) for spatial modelling to visualise pollutant distribution and used linear regression to develop a distance recommendation model. The results revealed a strong correlation between CO₂ and TVOC concentrations and traffic volume, whereas PM2.5 levels were more influenced by atmospheric conditions. The air quality index (AQI) classification indicated a shift toward